A Conceptual Model of Sustainable Technology Use: The Role of Confirmation and Perceived Usefulness in the Hospital X Management Information System in Padang - Adhyka, Nurmaines; Rahmaddian, Tosi; Yurizali, Bun; Ramadoni; Wulandani, Yolanda Putri (International Journal of Statistics in Medical Research, 2025)
Background and Objective: The adoption and use of Management Information Systems (MIS) in healthcare settings, like Hospital X in Padang, are crucial for improving operational efficiencies and patient care. Task-Technology Fit (TTF) measures how well technology supports its intended tasks and significantly influences user satisfaction and system use continuity. Key factors include Confirmation, assessing post-adoption user expectations, and Perceived Usefulness (PU), evaluating job performance enhancement. This study explores TTF’s impact on Continuance Intention (CI), mediated by Confirmation and PU, within Hospital X’s MIS context. Methods: Data were gathered from staff at H.B. Saanin Mental Hospital, one of West Sumatera’s public hospitals. A total of 158 questionnaires were distributed, with 150 deemed analyzable using structural equation modeling. Result: The study finds no statistically significant relationship between TTF and PU. However, a marginally significant relationship between TTF and Confirmation suggests modest evidence that alignment between tasks and technology influences users’ confirmation of their expectations. Notably, PU does not directly impact CI within Hospital X’s MIS, nor does Confirmation significantly affect users’ intention to continue using the system. Overall, the direct influence of technology-task alignment on users’ intention to continue using MIS is inconclusive in this study context. Conclution: This study reveals complex relationships among TTF, Confirmation, PU, and CI within Hospital X’s MIS framework. Despite the theoretical significance of TTF and Confirmation, their direct impacts on PU and users’ intention to continue system use are not statistically significant. These findings emphasize the ongoing need to evaluate and adapt MIS strategies to better align with user needs and ensure sustained effectiveness in healthcare operations.